PEMAHAMAN KONSEP PERSAMAAN NILAI MUTLAK DITINJAU DARI KEMANDIRIAN BELAJAR SISWA KELAS X SMA - Ellawati Safitri; Dede Suratman; Halini Halini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe facts show that students' understanding of the concept of absolute value is still in low classified. The lack of understanding of student concepts is influenced by several factors, one of which is lack of student confidence in working on problems. self confidence is one part of student learning independence. Therefore this study aims to describe the understanding of the concept of the absolute value equation in terms of student learning independence. The research method used is descriptive qualitative in the form of case studies. Subjects were thirty-eight students in SMA Negeri 2 Pontianak. The results of this study indicate that students' understanding of concepts is balanced with learning independence. students who have a high level of learning independence overall the results of the concept understanding test are also high. students who have a level of independence of learning while overall the results of the test understanding of the concept are also being. students who have low levels of learning independence overall the results of the concept understanding test are also low. The conclusion from study's result showed that level the high student's independence learning, the level student's concept understanding was high also.Keywords: Absolute Value Equations, Concept Understanding, Learning                  Independence